Clinical efficacy of Ahmed glaucoma valve implantation combined with 23-gauge vitrectomy for medically uncontrolled neovascular glaucoma with proliferative diabetic retinopathy - Lin, Zhong-Jing (Int J Ophthalmol, 2020)
AIM: To describe the clinical results of combined Ahmed valve implantation and 23-gauge vitrectomy for medically uncontrolled neovascular glaucoma (NVG) secondary to proliferative diabetic retinopathy (PDR). METHODS: The medical records of medically uncontrolled NVG patients with PDR who underwent Ahmed valve implantation and 23-gauge vitrectomy between March 2016 and December 2018 were reviewed. Enrolled patients had at least 6-month follow-up. Panretinal photocoagulation (PRP), anti-vascular endothelial growth factor, surgery and medication history were documented. RESULTS: Eleven eyes of 11 patients were included in our study. The visual acuity improved in 8 eyes and remained unchanged in 3 eyes. The preoperative intraocular pressure (IOP) was significantly decreased at the last follow-up (48.8±4.3 to 17.0±1.5 mm Hg, P<0.001). All eyes needed three topical anti-glaucomatous medications before surgery, but the number was significantly reduced to 0.72±0.19 at the last visit (P<0.001). Four eyes had choroidal detachment and 3 eyes had minor hyphemia, all of which gradually resolved without treatments in one week. CONCLUSION: Ahmed glaucoma valve implantation combined with 23-gauge vitrectomy might be a safe and alternative treatment for NVG with PDR.